A perspective for chronic obstructive pulmonary disease (COPD) management: six key clinical questions to improve disease treatment. (4th March 2021) - Contoli, Marco; Morandi, Luca; Di Marco, Fabiano; Carone, Mauro
ABSTRACT: Introduction: In 2011, the GOLD recommendations for the treatment of Chronic Obstructive Pulmonary Disease (COPD) introduced new clinical elements to classify the severity of the disease and to guide pharmacological choice. For the first time in the GOLD documents, treatment decision was no longer guided only by pulmonary function, but by a more complex combination of pulmonary function and clinical aspects. The recent versions of the GOLD recommendations introduce new aspects for the clinicians and pose new question for the management of the disease. In addition, inflammatory biomarkers and blood eosinophil levels, have been considered to guide treatment selection. Area covered: The evolution of disease management proposed by the GOLD document opens several areas of debate. A series of roundtable discussions among respiratory physicians took place in Italy to address key clinical questions. Particularly, the role of lung function and the use of biomarkers, the adherence to international guidelines and the possibility to personalize the pharmacological approach in COPD patients have been discussed, summarized and analyzed. Expert opinion: The authors believe that the development of a precision medicine approach tailoring the specific treatment for each patient is the goal of COPD management and may be achieved by considering the phenotypic classification of COPD patients.